Nutritional and Sensory Profile of Conventional, Gluten-Free, and Plant-Based Cookies - Puspitasari, Elia Devina; Tjie Kok (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2025)
Abstract—Amid the growing consumer demand for healthier and more sustainable food options, gluten-free and plant-based cookies have emerged as key alternatives to conventional products. This review provides a comparative analysis of the composition, nutrition, and sensory acceptance of these three cookie types to identify challenges and opportunities for innovation. Key findings indicate that while alternative cookies address specific dietary needs, major challenges lie in replicating texture and achieving nutritional balance. Critically, this review highlights the unique contribution of utilizing local composite flours such as gadung tuber, brown rice, and moringa leaves as a proven solution to significantly enhance both nutritional value and textural quality. The practical implication is that future cookie formulation innovation relies heavily on leveraging local, functional ingredients to create products that are not only nutritionally superior but also widely accepted by consumers. Keywords: cookies, alternative flours, functional foods, consumer behavior, nutritional profile, sustainability Abstrak—Seiring meningkatnya permintaan konsumen akan pilihan makanan yang lebih sehat dan berkelanjutan, kue kering bebas gluten dan berbasis nabati telah muncul sebagai alternatif utama dari produk konvensional. Review ini menyajikan analisis komparatif mengenai komposisi, nutrisi, dan penerimaan sensoris dari ketiga jenis kue kering tersebut untuk mengidentifikasi tantangan dan peluang inovasi. Temuan utama menunjukkan bahwa meskipun kue kering alternatif mengatasi kebutuhan diet spesifik, tantangan utama terletak pada replikasi tekstur dan keseimbangan nutrisi. Secara kritis, review ini menyoroti kontribusi unik dari pemanfaatan tepung komposit lokal seperti umbi gadung, beras merah, dan daun kelor sebagai solusi yang terbukti efektif untuk meningkatkan nilai gizi dan kualitas tekstur secara signifikan. Implikasi praktisnya adalah bahwa inovasi formulasi cookies di masa depan sangat bergantung pada pemanfaatan bahan fungsional lokal untuk menciptakan produk yang tidak hanya unggul secara nutrisi tetapi juga dapat diterima secara luas oleh konsumen. Kata kunci: keberlanjutan, kue kering, pangan fungsional, perilaku konsumen, profil nutrisi, tepung alternatif